Proses Pembuatan Busana Pesta Malam Dengan Variasi Spiral - Mien Zyahratil Umami; Irawati Fajrin (Garina, 2020)
Evening party clothes are clothes worn at night parties. The fashion made in this final project is evening party dress with a cut above the knee and a spiral variation that adds to the beauty of the outfit. This spiral variation gives a unique impression, simple but still elegant and beautiful when used. The spiral variation is made by cutting the fabric such as insect repellent. The purpose of making this final project is to determine the process of making evening party dresses with spiral variations. The method used in the process of making evening party dresses with spiral variations includes: library methods, observation methods, documentation methods and data analysis. The result of the process of making evening party dresses with spiral variations in the making of this final project is the creation of evening party dresses according to the design made by the author. The process of making evening party dresses with spiral variations is a series of activities which include: determining the design, preparing tools and materials, taking measurements, making basic patterns, breaking patterns, cutting, gluing tricots, meradering, sewing, finishing. The party outfit tonight has two pieces of clothing, namely: a dress and a robe. This evening party dress has a spiral variation that adds to the impression of a unique outfit, simple but still elegant and beautiful when worn.